Unraveling the Variability of Essential Oil Composition in Different Accessions of Bunium persicum Collected from Different Temperate Micro-Climates - Mudasir Hafiz Khan; Niyaz Ahmad Dar; Bashir Ahmad Alie; Sher Ahmad Dar; Ajaz Ahmad Lone; Ghulam Hassan Mir; Uzma Fayaz; Sajad Ali; Anshika Tyagi; Mohamed A. El-Sheikh; Saleh Alansi (Molecules, 2023)
The present investigation was performed to evaluate the variability of the essential oil composition present in the seed extract of Kala zeera (Bunium persicum Bioss.) obtained from different geographical zones of Northwestern-Himalayan using Gas Chromatography-Mass Spectrum (GC-MS). The results of the GC-MS analysis revealed significant differences in the essential oil content. Significant variability was observed in the chemical constituents of the essential oils mainly for p-cymene, D-limonene, Gamma-terpinene, Cumic aldehyde and 1, 4-p-menthadien-7-al. Among these compounds, the highest average percentage across the locations was observed for gamma-terpinene (32.08%) which was followed by cumic aldehyde (25.07%), and 1, 4-p-menthadien-7-al (15.45%). Principal component analysis (PCA) also grouped the 4 highly significant compounds i.e., p-Cymene, Gamma-Terpinene, Cumic aldehyde, and 1,4-p-Menthadien-7-al into same cluster which are mainly distributed in Shalimar Kalazeera-1, and Atholi Kishtwar zones. The highest value of gamma-terpinene was recorded in Atholi accession (40.66%). However, among climatic zones Zabarwan Srinagar and Shalimar Kalazeera-1 was found to have highly positive significant correlation (0.99). The cophenetic correlation coefficient (c) was found to be 0.8334 during hierarchical clustering for 12 essential oil compounds showing that our results are highly correlated. Network analysis also showed the overlapping pattern and similar interaction between the 12 compounds as shown by hierarchical clustering analysis. From the results, it could be concluded that existence of variability among the various bioactive compounds of B. persicum which are probably to be incorporated to the potential list of drugs and may serve as good genetic source for various modern breeding programs.